Hospital-Acquired Urinary Tract Infections: Results of a Cohort Study Performed in an Internal Medicine Department - Lobão, MJ (2017)
Introduction: Urinary tract infections are the most frequent healthcare associated infections, being related to both high costs and morbidity. Our intention was to carry out an epidemiological characterization of hospital acquired urinary tract infections that occurred in an internal medicine department of a Portuguese hospital. Material and methods: Retrospective cohort study (historic cohort). Data were analysed from a systematic random sample of 388 patients, representative of the 3492 admissions occurred in 2014 in that department. Results: One in four patients underwent the placement of a bladder catheter [24.7% (n = 96); 95% CI: 20% - 29%], 36.5% (95% CI: 33% - 48%) of which in the absence of clinical criteria for that procedure. The global cumulative incidence rate for nosocomial urinary tract infections was 4.6% (95% CI: 2.5% - 6.7%). Most hospital acquired urinary tract infections (61.1%) were related to bladder catheter use. We quantified 3.06 infections / 1000 patient-days and 14.5 infections / 1000 catheter-days. Catheter associated urinary tract infection occurred at an early stage of hospitalization. The vast majority of patients (66.7%) that developed a catheter associated urinary tract infection were subjected to bladder catheter placement at emergency department. Seventy one per cent of catheter associated urinary tract infection occurred in patients that were subjected to bladder catheter placement without criteria. Discussion: These results point to an excessive and inadequate use of urinary catheters, highlighting the need for judicious use taking into account the formal clinical indications. The incidence of catheter associated urinary tract infection is similar to what we found in other studies. Nevertheless we found a very high incidence density per catheter-days that may foresee a problem probably related to the absence of early withdrawal of the device, and to both bladder catheter placement and maintenance practices. A significant part of catheter associated urinary tract infection occurred in patients that had the bladder catheter placed in the emergency department, before the admission to the internal medicine ward, which highlights the need to assess the urinary catheterization practices in those departments. Conclusion: The high rate of catheter associated urinary tract infection that occurred in the absence of bladder placement indication reinforces the need to implement prevention strategies that contemplate the reduction of its use. Emergency departments should be part of quality improvement projects in this area. Causes for the early onset of catheter associated urinary tract infection in this cohort should be investigated.